IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON THE FINANCIAL RESULTS OF CEMENT MANUFACTURING ENTERPRISES - KASPRUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the impact of corporate social responsibility of cement companies on their financial results. The assessment of the impact of CSR on the financial results of cement manufacturers was carried out using the example of China National Building Material Co Ltd (CNBM), which is the world leader in cement production. For the assessment, correlation analysis was used using such dependent variables as operating income and total profit, as well as independent variables: the number of organized employee training programs, the number of academic degrees received by employees with the support of the company, investments in occupational safety, the number of volunteer groups created, investments to support volunteer activities, the number of volunteer employees, the time of providing volunteer services, social security expenses, the number of social security projects, the number of employees participating in corporate pension schemes. The results of the correlation analysis demonstrate a close relationship between social initiatives implemented within the framework of corporate social responsibility and financial performance indicators, which indicates the financial feasibility of investing in the social direction of CSR. One of the most powerful determinants is the cost of social security for employees, as well as the number of projects in this area. A significant positive relationship was also found between the volunteer activity of employees and financial indicators. Educational initiatives aimed at personnel development also demonstrate a positive correlation with financial performance. A linear regression model of the dependence of operating income on social security costs of the form y=0.1082x+2361.3 was constructed. The value of the coefficient of determination R2=0.8377 indicates a high quality of approximation. The results of the study confirm the feasibility of integrating social initiatives into the strategic development of cement production enterprises.